BREACH OF PSYCHOLOGICAL CONTRACTS AND DISCRETIONARY BEHAVIOUR IN NIGERIAN ACADEMICS - Akeem Ayofe 'Akinwale; Adetunji Oluseyi Shadare; Mustapha Olanrewaju Aliyu (Journal of Business Management and Accounting, 2021)
This study explored the breach of psychological contracts and discretionary behaviour by Nigerian academics. A survey was employed to elicit information from 378 academics that were randomly selected from 7,131 academics in federal universities in the North-Central Nigeria. The results from the hypotheses testing revealed that most of the universities in the North-Central zone did not comply with the psychological contract (as supported by the negative results  from statistical estimates and Leveneâ€™s t-values). There was a positive correlation between breach of psychological contract and organisational  citizenship behaviour (OCB) as well as positive relationship between breach of psychological contract and deviant workplace behaviour (DWB) (r=0.196; p<0.05 and r=0.126; p<0.05, respectively). The breach of psychological contract has influenced academics in different ways showing a tendency for OCB and DWB. Unfortunately, the tendency for DWB outweigh that of OCB. Therefore, academics who uphold OCB despite the perceived BPC should be encouraged to sustain their good behaviour.